Comparison of Properties of Single Jersey Knit Fabrics Knitted With Single and Double Ply Yarn of Same Resultant Count - Reza, Mohammad Hosain (European Scientific Journal, ESJ, 2017)
The constructional properties of a weft knitted fabric depends on stitch length and yarn count. In this paper it is searched that whether yarn ply affects the properties of weft knitted fabric though knitted from yarns of same resultant count. For this fabric samples were knitted with pairs of single ply and double ply yarns with the same resultant count. Then the constructional properties like course / cm, wales / cm, stitch density, G.S.M. and spirality were measured. 10 data for each property from each sample were taken and averaged. From the averaged data graphs were constructed to make the comparison. From the graphs it is found that the properties (i.e. is course / cm, wales / cm, stitch density, G.S.M) is less in all of the sample knitted from double ply yarns than the fabric samples knitted from single ply yarns. Moreover though the fabric samples were made by the same settings of knitting machine but the stitch length is more in fabric samples knitted by double ply yarns. As the component yarns lose twist during doubling and twisting they become bulkier. For this stitches occupied more spaces in fabric made from double ply yarn. This lead to make the difference in constructional properties between fabric samples made from single ply yarns and double ply yarns of same resultant count.